Establishing and operating a 'virtual ward' system to provide care for patients with COVID-19 at home: experience from The Gambia. Issue 6 (17th June 2021) - Wariri, Oghenebrume; Okomo, Uduak; Cerami, Carla; Okoh, Emmanuel; Oko, Francis; Jah, Hawanatu; Bojang, Kalifa; Susso, Bubacarr; Olatunji, Yekini; Nkereuwem, Esin; Akemokwe, Fatai Momodou; Jobe, Modou; et al.
Abstract : Health systems in sub-Saharan Africa have remained overstretched from dealing with endemic diseases, which limit their capacity to absorb additional stress from new and emerging infectious diseases. Against this backdrop, the rapidly evolving COVID-19 pandemic presented an additional challenge of insufficient hospital beds and human resource for health needed to deliver hospital-based COVID-19 care. Emerging evidence from high-income countries suggests that a 'virtual ward' (VW) system can provide adequate home-based care for selected patients with COVID-19, thereby reducing the need for admissions and mitigate additional stress on hospital beds. We established a VW at the Medical Research Council Unit, The Gambia at the London School of Hygiene and Tropical Medicine, a biomedical research institution located in The Gambia, a low-income west African country, to care for members of staff and their families infected with COVID-19. In this practice paper, we share our experience focusing on the key components of the system, how it was set up and successfully operated to support patients with COVID-19 in non-hospital settings. We describe the composition of the multidisciplinary team operating the VW, how we developed clinical standard operating procedures, how clinical oversight is provided and the use of teleconsultation and data capture systems to successfully drive the process. We demonstrate that using a VW to provide an additional level of support for patients with COVID-19 at home is feasible in a low-income country in sub-Saharan Africa. We believe that other low-income or resource-constrained settings can adopt and contextualise the processes described in this practice paper to provide additional support for patients with COVID-19 in non-hospital settings.